Jewish law: new perspectives - Stone, Suzanne Last; Brafman, Yonatan Y. (Perspectives on Jewish texts and contexts, 2025)
New Perspectives on Jewish Law combines the detailed work characteristic of scholarship on Jewish law with an orientation towards its broader academic and cultural significance. It shifts the study of Jewish law from its focus on legal doctrine and history to legal theory, achieving in the process a more sophisticated understanding of law that will benefit both the legal academy and Jewish studies. By employing the framework of legal theory, it similarly corrects an over-emphasis on the metaphysical presuppositions and philosophical implications of Jewish law, which has tended to cast it as exceptional relative to other legal systems. Moreover, it answers to old-new anxieties about law, often symbolized by Judaism, raised by contemporary feminists and by philosophers who are animated by recent interpretations of Paul through actual engagement with the Jewish legal tradition. The volume consists of three parts. The first focuses on the critique of positivism, its implications, and the new directions that it opens up for the analysis of Jewish law. The second part takes stock of recent methodological developments in the study of Jewish legal texts and investigates the relation between Jewish law and the disciplines, including history, literary theory, ritual studies, the digital humanities, as well as traditional approaches to Jewish learning. It concludes with a reflection on these interdisciplinary contributions from the perspective of legal theory. The third part explores the connections among Jewish law, philosophy, and culture critique. It assesses the relation or lack thereof between Jewish law and modern Jewish thought, and examines specific issues of philosophical interest, including truth and normativity. It also investigates the image of Jewish law in the contemporary critique of law as well as how Jewish law could productively contribute to that debate. It concludes with a reflection on these studies from the perspective of philosophy of law